Pengaruh Media Eyelearn Berbasis Articulate Storyline 3 Terhadap Keterampilan Berpikir Kritis Siswa di Sekolah Dasar - Bela Dwi Nur Cahyani; Aan Widiyono (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyse the effect of using the Eyelearn platform, based on Articulate Storyline 3, on improving the critical thinking skills of primary school pupils regarding the topic of the sense of sight in Integrated Science Education (IPAS) lessons. The study employed a quantitative approach using a pre-experimental design of the one-group pretest–posttest type. The research subjects consisted of 28 Year 5 pupils at Wonorejo State Primary School 1. Data were collected via multiple-choice tests designed based on critical thinking skill indicators and administered before and after the intervention. Data analysis included the Shapiro–Wilk normality test and a paired-sample t-test. The results showed an increase in the mean score from 52.7 in the pre-test to 78.6 in the post-test, with an effect size classified as very large (Cohen’s d = 2.15). These findings indicate that the use of the Articulate Storyline 3-based Eyelearn platform has a significant effect on improving pupils’ critical thinking skills. Consequently, this platform is suitable for use as an alternative for IPAS learning in primary schools to support the development of critical thinking skills